2008
DOI: 10.1016/j.nlm.2007.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Co-induction of long-term potentiation and long-term depression at a central synapse in the leech

Abstract: Most studies of long-term potentiation (LTP) have focused on potentiation induced by the activation of postsynaptic NMDA receptors (NMDARs). However, it is now apparent that NMDAR-dependent signaling processes are not the only form of LTP operating in the brain (Malenka and Bear, 2004). Previously, we have observed that LTP in leech central synapses made by the touch mechanosensory neurons onto the S interneuron was NMDAR-independent (Burrell and Sahley, 2004). Here we examine the cellular mechanisms mediating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 27 publications
(45 reference statements)
1
24
0
Order By: Relevance
“…1A) consists of both a monosynaptic electrical component and a polysynaptic, glutamatergic component (Muller and Scott 1981;Li and Burrell 2008), although the identities of the interneurons that mediate the glutamatergic component are not known. Previous studies have shown that this synaptic circuit can undergo LTP and LTD as a result of tetanic stimulation and low-frequency stimulation (LFS), respectively (Burrell and Sahley 2004;Burrell and Li 2008;Li and Burrell 2009), but it was unknown whether pairing of T-and S-cell activity results in persistent changes in synaptic signaling.In this paper, both LTP and LTD were observed following pairing spike trains that mimic the physiologically relevant patterns of T-and S-cell activity during whole-body shortening. The pattern of this plasticity was similar to that observed during STDP; LTP following presynaptic-before-postsynaptic pairings and LTD following postsynaptic-before-presynaptic pairings.…”
mentioning
confidence: 99%
“…1A) consists of both a monosynaptic electrical component and a polysynaptic, glutamatergic component (Muller and Scott 1981;Li and Burrell 2008), although the identities of the interneurons that mediate the glutamatergic component are not known. Previous studies have shown that this synaptic circuit can undergo LTP and LTD as a result of tetanic stimulation and low-frequency stimulation (LFS), respectively (Burrell and Sahley 2004;Burrell and Li 2008;Li and Burrell 2009), but it was unknown whether pairing of T-and S-cell activity results in persistent changes in synaptic signaling.In this paper, both LTP and LTD were observed following pairing spike trains that mimic the physiologically relevant patterns of T-and S-cell activity during whole-body shortening. The pattern of this plasticity was similar to that observed during STDP; LTP following presynaptic-before-postsynaptic pairings and LTD following postsynaptic-before-presynaptic pairings.…”
mentioning
confidence: 99%
“…It is not clear whether this variation is due to differences intrinsic to the different synapses, differences in the stimulation protocols used to induce LTP/LTD, or both. Our studies in other synapses used either tetanic stimulation or low frequency stimulation to induce LTP and LTD, respectively (Burrell and Sahley, 2004;Burrell and Li, 2008;Li and Burrell, 2009;Yuan and Burrell, 2010), or used more pairings of presynaptic and postsynaptic activity than utilized in the current study [5 in the present study versus 10 pairings in another recent study (Li and Burrell, 2011)]. It is possible that these other studies stimulated the synapses in a strong enough manner to overcome any seasonal influences on LTP or LTD.…”
Section: Discussionmentioning
confidence: 98%
“…The type of LTP and LTD depends on the synapse [15]. LTP and LTD are dependent on several molecular players including receptors, enzymes, and several signaling molecules such as hormones, neurotransmitters, peptides, and ions [16,17]. The transmitter molecules implicated in LTP and LTD induction include dopamine, glutamate, noradrenaline, serotonin, and acetylcholine [18][19][20].…”
Section: Mechanisms Of Neurometaplasticitymentioning
confidence: 99%
“…Ca 2+ channels, sodium channels, transient receptor potential vanilloid), transporters (dopamine transporter, serotonin transporter, etc.) [13,16,36]. The enzymes involved in neurometaplasticity are calmodulin-dependent kinase II (CaMKII), protein kinase A (PKA), protein kinase C (PKC), cAMP-dependent protein kinase (PKA), tyrosine kinase src (Src), mitogen activated protein kinases (MAPK), phospholipases, phosphatidylinositol-3-kinase, among others [16][17][18][19][37][38][39].…”
Section: Mechanisms Of Neurometaplasticitymentioning
confidence: 99%
See 1 more Smart Citation